Effects of Work Immersion on the Academic Performance of Senior High School Students - Tañalas, Jessa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effects of work immersion on the academic performance of Senior High School students in selected public secondary schools in the Binangonan District, Schools Division Office of Rizal, during the School Year 2025–2026. Specifically, it examined the perceived effects of work immersion on students' motivational drive, class interaction, critical thinking skills, and task accomplishment, as well as the relationship of these factors with their academic performance. The study employed a descriptive survey research design complemented by documentary analysis. A total of 345 Grade 12 students were selected from a population of 2,415 using Slovin’s formula and simple random sampling. Data were gathered through a researcher-made questionnaire-checklist, while students' average grades were obtained through documentary analysis to determine their academic performance. Descriptive and inferential statistical tools were utilized in analyzing the data. Findings revealed that most respondents were male, third-born among siblings, belonged to families with more than two children, had a monthly family income of ₱15,000 and above, and had parents who were college undergraduates or graduates engaged in employment or self-employment. Students perceived work immersion to have a high effect on their motivational drive, class interaction, critical thinking skills, and task accomplishment. Significant differences were found in the perceived effects of work immersion when respondents were grouped according to their demographic profile. The respondents attained a Very Satisfactory level of academic performance based on their average grades. Moreover, a significant relationship existed between the perceived effects of work immersion and students' academic performance, indicating that positive work immersion experiences contribute to better academic outcomes. The study concluded that learners' demographic characteristics influence their perceptions of work immersion and that work immersion significantly contributes to their academic performance. It is recommended that schools strengthen industry partnerships, provide meaningful immersion experiences, address challenges encountered during implementation, and adopt the proposed action plan to further enhance students' preparedness for higher education, employment, and lifelong learning.
Keywords: Work Immersion, Academic Performance, Senior High School Students, Motivational Drive, Class Interaction, Critical Thinking Skills, Task Accomplishment